Early Marriage in Women and the Risk of Low Birth Weight - Azinar, Muhammad; Fibriana, Arulita Ika; Nisa, Alfiana Ainun; Rahfiludin, Mohammad Zen; Indrianto, Gunawan Sapto; Sholahuddin, Irfan; Tamalla, Putri Nur; Permatasari, Claudia (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Neonatal mortality, largely caused by Low Birth Weight (LBW), is a big challenge in Grobogan district, Central Java. For instance, the year 2020 recorded 111 infant mortality cases due to LBW. The following year, an additional 63 cases were reported from January- July bringing the total to 174 instances recorded in less than two years. Early marriage in women has been touted as the cause of the high LBW witnessed. Notably, Law Number 16 of 2019 set the base age at 19 years for marriage for both men and women. Statistics show that a total of 380 women got married at 19 years in 2020. However, the cases have significantly heightened to 453 in the year 2021. The research sample for this study was drawn from babies born to women aged 30 and below. The data was analyzed using the Chi-square test, whose results confirmed that residence, level of education, and employment status were related to the incidence of early marriage in women. Furthermore, it was found that women who married at 20 years and below had a greater risk (1,728 times) compared to those who gave birth between 20-30 years.